Application of a taxi-based mobile atmospheric monitoring system in Cangzhou, China. (September 2020) - Wu, Yizheng; Wang, Yuxin; Wang, Lewen; Song, Guohua; Gao, Jian; Yu, Lei
Highlights: Application of a taxi-based mobile monitoring system in developing countries. A comparison between mobile monitoring data and fixed regulatory monitoring data. Analysis of spatial and temporal air pollution variations in a complex urban area. Abstract: Increasing air pollution as a result of rapid urbanization is of growing concern worldwide, particularly in populous developing countries. Sparse routine monitoring stations are not sufficient to capture the heterogeneity of air pollution levels in complex urban regions. In this study, a taxi-based mobile atmospheric monitoring system was applied to map the air pollution levels in Cangzhou, China. Fifty taxis equipped with particulate matter (PM) sensors were used to characterize the spatial and temporal variability of PM pollutants. Statistical analyses indicate that the mobile system can provide comparable data to that of fixed monitoring stations and help map the urban air quality. Moreover, the high-resolution air pollution map provided by the mobile monitoring system could address current data gaps, thereby providing valuable information to protect the public health and guide policy design.